Проблеми дослідження та збереження культурної спадщини м. Зіньків Полтавської області - Єрзіна, І.В.; Томілович, Л.В. (Сіверщина в історії України, 2021)
Стаття присвячена дослідженню історико-культурної спадщини м. Зіньків Полтавської області. Мета дослідження – обстеження об’єктів культурної спадщини міста, що перебувають на державному обліку, та виявлення тих об’єктів, які мають історичну, архітектурну, мистецьку цінність і потребують взяття на державний облік. The article is devoted to the study of historical and cultural heritage of Zinkiv, Poltava region. Zinkiv is a city in Poltava region, the administrative center of the district with the same name. The city is located on the Tashan River, a left tributary of the Psel River (a tributary of the Dnipro), 80 km northwest of the regional center - Poltava, in the northern part of the region. Natural conditions had a significant impact on the historical development of the city throughout the period of its existence. During the late Middle Ages (at time when its continuous existence has been recorded, since the 30’s years of the XVII century) Zinkiv was at the crossroads of important paths, the most important of which led from Poltava to Chernihiv to Hadiach. There are high right banks of the river Tashan at the point of loop, swampy floodplain of the river, especially of its left bank, the presence of streams, which flow into the Tashan River, and ravines in this place, a fairly large plateau, convenient for settlement. All these together created conditions to the founding of the city and its fortifications in the turbulent times of the XVII century. Today, the history of the city has many gaps, especially in terms of early stages of its existence, due to the lack of archaeological research on the territory of the historical core of the city and insufficient provision of written and cartographic sources of the period XVII – early XVIII centuries. Therefore, for example, such issues as the location of the castle on its territory, the size of the city next to it, the stages of development of these urban formations during the XVII–XVIII centuries remain unresolved in Zinkiv history. The results of area research of Zinkiv cultural heritage in comparison with the lists of registered cultural heritage sites showed that there are also many gaps in this area that need to be filled. At present, the total number of cultural heritage sites on the state register in the territory of Zinkiv is 27. Of them: 1 architectural monument of local significance, 22 historical monuments of local significance, 1 monumental art monument of local significance, 3 newly discovered objects of cultural heritage (2 of them by type of historical, 1 – monumental art). According to the results of field surveys, another 28 cultural heritage sites are proposed for registration. Of these: 15 – by type of architecture, 3 – by type of historical, 1 – by type of history and science and technology, 9 – archaeological. These statistics illustrates how underestimated Zinkiv cultural heritage is currently.